2014
DOI: 10.3126/dsaj.v7i0.10443
|View full text |Cite
|
Sign up to set email alerts
|

Religious Culture and Medicinal Plants: An Anthropological Study

Abstract: This study is based on primary data collection from the field from January 2011 to September 2013 to satisfy the query about the relation between religious culture and the medicinal plants. This study was carried out in Brahmin/ Chhetry dominated community of Baglung district of western development region of Nepal. The data were collected by using participant observation and interview. From this study it is found that, Brahmin/Chhetry use 48 plant species in their ritual, festivals and ceremony. Similarly they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…Hanuman and Lord Shani for blessings in Maharashtra (Pawar 2020). The use of flowers of Calotropis gigantea for worshipping in the present study is similar to that reported in Nepal, where it is considered religious and used in child naming ceremonies (Nwaran) (Sapkota 2013;Sharma 2020). This Ayurvedic plant also has essential medical characteristics such as antifungal, antipyretic, analgesic, expectorant, anti-inflammatory, and anti-rheumatic (Meena et al 2011).…”
Section: )supporting
confidence: 87%
“…Hanuman and Lord Shani for blessings in Maharashtra (Pawar 2020). The use of flowers of Calotropis gigantea for worshipping in the present study is similar to that reported in Nepal, where it is considered religious and used in child naming ceremonies (Nwaran) (Sapkota 2013;Sharma 2020). This Ayurvedic plant also has essential medical characteristics such as antifungal, antipyretic, analgesic, expectorant, anti-inflammatory, and anti-rheumatic (Meena et al 2011).…”
Section: )supporting
confidence: 87%
“…In terms of beliefs, for instance, based on Balinese Hinduism, many flowers have an important role in religious ceremonies (Sujarwo et al 2020). Like in Bali, other local communities around the world have a tradition in socio-cultural and religious aspects, including beliefs, folk religions, closely associated with health practices, rituals, festivals, ceremonies and other religious activities (Sapkota 2013;Husti and Canto 2015;Mir et al 2018;Quiroz and van Andel 2018;Vardhana 2018;Sutrisno et al 2020). Based on the beliefs, traditional ceremonies of the communities as part of human cultural products at a practical level cannot be separated from the use of natural resources, mainly plants.…”
Section: Discussionmentioning
confidence: 99%
“…Some ceremonial and ritual acts are common in every religions, which focus on sacred objects and symbols with the supernatural power (Sapkota 2013). People worship them as icons of Gods and Goddesses, thereby grown or protected with special care (Manandhar 2002).…”
Section: Discussionmentioning
confidence: 99%